2009
DOI: 10.1108/s0731-9053(2009)0000024013
|View full text |Cite
|
Sign up to set email alerts
|

The stock of money and why you should care

Abstract: In this paper, I will examine the problems created by incorrectly using a simple sum monetary aggregate to measure the monetary stock. Specically, I will show that simple sum monetary aggregate confounds the current stock of money with the investment stock of money and that this confounding leads the simple sum monetary aggregate to report an articially smooth monetary stock. This smoothing causes important information about the dynamic movements of the monetary stock to be lost. This may oer at least a partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Barnett, Chae, and Keating (2005) and Barnett, Keating, and Kelly (2008) argue that because of this confounding, the official monetary aggregates confound the money stock with the present value of the investment yield returned by monetary assets, and thus significantly over-state the money stock. Kelly (2009) showed that this confounding causes simple-sum aggregates to fail to capture the true relationship between the economic money stock and interest rates. Finally, Kelly, Barnett, and Keating (2011) argues that much of the liquidity puzzle can be explained by the measurement error exhibited by simple-sum aggregation.…”
Section: Iwhmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnett, Chae, and Keating (2005) and Barnett, Keating, and Kelly (2008) argue that because of this confounding, the official monetary aggregates confound the money stock with the present value of the investment yield returned by monetary assets, and thus significantly over-state the money stock. Kelly (2009) showed that this confounding causes simple-sum aggregates to fail to capture the true relationship between the economic money stock and interest rates. Finally, Kelly, Barnett, and Keating (2011) argues that much of the liquidity puzzle can be explained by the measurement error exhibited by simple-sum aggregation.…”
Section: Iwhmentioning
confidence: 99%
“…These problems can only be addressed by carefully measuring money using 1 This includes the seminal contributions of Gordon and Leeper (1994), Leeper, Sims, and Zha (1996) Bernanke andMihov (1998), Christiano, Eichenbaum, andEvans (1996) and Christiano, Eichenbaum, and Evans (1999). 2 See, e.g., Barnett and Serletis (2000), Barnett, Chae, and Keating (2005), Barnett, Keating, and Kelly (2008), Barnett and Chauvet (2011), Kelly (2009), and Kelly, Barnett, and Keating (2011 The remainder of the paper is structured as follows. Since the use of Divisa money is quite unusual in this literature, sections two and three will start by introducing the dataset and giving a brief descriptive analysis of the core developments.…”
mentioning
confidence: 99%
“…Dubbed the "output puzzle," "liquidity puzzle," and "price puzzle," 2 respectively, these and other puzzling results have become a standard criticisms of using monetary aggregates to measure monetary policy shocks. We contend, contrarily, that the failure of monetary aggregates to properly capture sensible dynamic responses does not constitute a general indictment against money but instead that the problem may stem from a poor informational content of the monetary aggregates that have been chosen (see, e.g., Kelly, 2009, Kelly et al, 2011, and Keating et al, 2013 who each provide empirical evidence that the these puzzles vanish when a properly measured monetary aggregate is used).…”
Section: Introductionmentioning
confidence: 96%
“…1) state "...if pressed on this issue, virtually all monetary economists today would no doubt concede that the Divisia aggregates proposed by Barnett are both theoretically and empirically superior to their simple-sum counterparts." For example, Barnett et al (2005) and Barnett et al (2008) find that simple sum aggregates significantly overstate the money stock, and Kelly (2009) and Kelly et al (2011) find that simple sum aggregates obfuscate the liquidity effect (an inverse relationship between money and interest rates following a change in monetary policy).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kelly (2009) showed that the first difference of CSM and the first difference of ISM are strongly negatively correlated. Since nt r is a function of interest rates, equations (9), (10) and (11) make it clear that the simple sum monetary aggregates fail to capture the true relationship between the economic money stock and interest rates.…”
Section: Decomposition Of the Simple Sum Monetary Aggregatesmentioning
confidence: 99%